2014
DOI: 10.1111/cei.12254
|View full text |Cite
|
Sign up to set email alerts
|

Immunological monitoring of extracorporeal photopheresis after heart transplantation

Abstract: SummaryExtracorporeal photopheresis (ECP) has been used as a prophylactic and therapeutic option to avoid and treat rejection after heart transplantation (HTx). Tolerance-inducing effects of ECP such as up-regulation of regulatory T cells (Tregs) are known, but specific effects of ECP on regulatory T cell (Treg) subsets and dendritic cells (DCs) are lacking. We analysed different subsets of Tregs and DCs as well as the immune balance status during ECP treatment after HTx. Blood samples were collected from HTx … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 31 publications
1
25
0
5
Order By: Relevance
“…The increase of T regs is considered to be the initial mode of action of ECP, 13 and previous studies reported significantly increased T regs following ECP. 12,15,19 Thus, an increasing percentage of T regs has been defined as one criteria for a successful ECP treatment after HTx. 15 pDCs are known to support the expansion and induction of T regs and the maintenance of tolerance.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The increase of T regs is considered to be the initial mode of action of ECP, 13 and previous studies reported significantly increased T regs following ECP. 12,15,19 Thus, an increasing percentage of T regs has been defined as one criteria for a successful ECP treatment after HTx. 15 pDCs are known to support the expansion and induction of T regs and the maintenance of tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral blood samples obtained from the patients were treated and stained as described previously. 15,17 In brief, T regs were defined as CD3 + /CD4 + /CD25 high /CD127 low cells. Subsets of DCs were quantified by stainings using lineage cocktail-1, HLA-DR, CD11c, and CD123.…”
Section: Flow Cytometric Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Методика применяется во всем мире в качестве терапии заболеваний, обусловлен-ных нарушением Т-клеточной системы иммуни-тета [2], и зарекомендовала себя как эффективный метод предупреждения и лечения отторжения при трансплантации сердца, легких и печени [3][4][5][6]. Из-вестны результаты нескольких исследований, где курсы ЭФХТ были с успехом использованы для ку-пирования устойчивых эпизодов отторжения почеч-ного аллотрансплантата (ПАТ) [7,8].…”
Section: Introductionunclassified